Human sulfotransferase SULT2B1 physiological role and the impact of genetic polymorphism on enzyme activity and pathological conditions - Alherz, Fatemah A. (Frontiers in Genetics, 2024)
Human SULT2B1gene is responsible for expressing SULT2B1a and SULT2B1b enzymes, which are phase II metabolizing enzymes known as pregnenolone and cholesterol sulfotransferase (SULT), respectively. They are expressed in several tissues and contribute to steroids and hydroxysteroids homeostasis. Genetic variation of the SULT2B1 is reported to be associated with various pathological conditions, including autosomal recessive ichthyosis, cardiovascular disease, and different types of cancers. Understanding the pathological impact of SULT2B1 genetic polymorphisms in the human body is crucial to incorporating these findings in evaluating clinical conditions or improving therapeutic efficacy. Therefore, this paper summarized the most relevant reported studies concerning SULT2B1 expression, tissue distribution, substrates, and reported genetic polymorphisms and their mechanisms in enzyme activity and pathological conditions.